2015
DOI: 10.2147/ieh.s88809
|View full text |Cite
|
Sign up to set email alerts
|

eHealth innovations in LMICs of Africa and Asia: a literature review exploring factors affecting implementation, scale-up, and sustainability

Abstract: Background: In many low-and middle-income countries (LMICs), health system challenges relating to weak governance, health workforce shortages, and geographic and economic barriers to care impede effective delivery of health services to those in need. The rapid development of information and communication technologies over the last few decades offers the potential for addressing some of these challenges with innovative solutions, especially if offered at scale. This review reflects on the features of larger and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 22 publications
1
55
0
Order By: Relevance
“…In addition to theory and content, length of intervention, mode of presentation and other technical issues could make the eHealth intervention easy to use and thereby increase its effect [122][123][124]. For example, several studies suggested that the intervention should be integrated with existing infrastructures, developed in platforms that enable participants to access the intervention via various devices, and tested carefully before launching the intervention to ensure usability [62,73].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to theory and content, length of intervention, mode of presentation and other technical issues could make the eHealth intervention easy to use and thereby increase its effect [122][123][124]. For example, several studies suggested that the intervention should be integrated with existing infrastructures, developed in platforms that enable participants to access the intervention via various devices, and tested carefully before launching the intervention to ensure usability [62,73].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of eHealth implementations is a challenging undertaking [9,38,39]. There are a few published evaluations on eHealth implementations [6,30,[40][41][42][43] especially in the developing countries [39]. The difficulty is because such evaluation does not focus on technology only but often needs to consider how the technology components interact with other processes in the eHealth implementation [44], which in turn broadens the scope of the evaluation [45,46].…”
Section: An Overview Of Ehealth Implementations Evaluationmentioning
confidence: 99%
“…Healthcare administrators and policymakers are expected to select interventions that increase the quality and efficiency of services, care, and support high performance of health systems [1][2][3]. The application of information and communication technology (ICT) is becoming more popular in healthcare management and has proved to improve the effectiveness, access, quality and efficiency of the healthcare systems [4][5][6][7]. The WHO [8] notes that the application of eHealth is necessary if universal health coverage is to be realised.…”
Section: Introductionmentioning
confidence: 99%
“…12 However, use of social media also places new demands on clinicians and health practitioners, in particular around ensuring that the information provided is of sufficient quality and that the privacy of patients is protected, 24 which have been shown to be major concerns among older users. 4,[25][26][27][28][29] Case Study 1: A voice-based service to provide individualized, real-time feedback to help control type 2 diabetes Kim et al 21 investigated the use of a "ubiquitous health care service" (known as u-health care), to support elderly patients with diabetes in Seoul, South Korea, to manage glucose control without causing hypoglycemia. Because ease of use was found to be a significant limitation in a previous study by the same authors, 31 patients in this study used a voice-based reporting system that allowed them to send health data, including information on blood glucose levels, diet, exercise habits, and medication adherence through to a u-health care center using their existing home or cellular telephone.…”
Section: Current Health Technologiesmentioning
confidence: 99%
“…To date, few published studies on health technologies have included robust evaluations of their effectiveness. 15,22,29,33,53 This is a particular issue for interventions that are relatively novel, such as robotics and 3D printing. However, there remain significant uncertainties as to the effectiveness of even established technologies.…”
Section: How Effective Are Health Technology Initiatives?mentioning
confidence: 99%